PENGARUH CUSTOMER EXPERIENCE DAN PRODUCT QUALITY TERHADAP CUSTOMER SATISFACTION MELALUI BUYING DECISION PRODUK OUTDOOR GEAR EIGER DI KOTA PEKANBARU - -, Muhammad Al Madani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This study was conducted with the aim of knowing the effect of Costumer Experience and, Product Quality on Customer Satisfaction through Buying Decision in Pekanbaru city community. The population in this study were the people of Pekanbaru city who had shopped at Eierg products in Pekanbaru City. Sampling in this study was carried out using purposive sampling technique using the hair et al. formula, so that the number of samples in this study were 135 respondents. The data analysis method of this study uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS software version 4.1.0.2. The results showed that there is a positive and significant influence between Costumer Experience on Buying Decision. There is a positive and significant influence between Product Quality on Buying Decision. There is a positive and significant influence between Buying Decision on Customer Satisfaction. There is a positive and significant influence between Costumer Experience on Customer Satisfaction through Buying Decision. There is a positive and significant influence between social media marketing on Costumer Satisfaction through Buying Decision. Keywords: Costumer Experience, Product Quality, Buying Decision and Costumer Satisfaction.